KA Development of E-Module Mikrotik Training Information Technology Teacher in the Field of Computer Network Engineering - Anshari, Khairul; Rukun, Kasman; Huda, Asrul (The Journal of Educational Development, 2019)
This research aims to develop module products in electronic or digital form about mikrotiks and reveal their validity and practicality. This type of research is the development of research using the ploomp and nieveen models, with three stages of development, namely 1) preliminary research 2) prototyping stage and 3) assessment stage. The instrument used was a questionnaire in the form of a validity questionnaire and a practicality questionnaire. The mikrotik training module was validated by six experts namely three mikrotik material experts and three module experts. The practicality of mikrotik e-modules is carried out on computer network engineering teachers in several State Vocational High Schools in Padang. The validity test results obtain results with a valid category. Based on the practicality test by the computer network engineering teacher at the State Vocational High School in Padang, the results obtained indicate that the module has a very high practicality category. Based on the results of this study, it can be concluded that the mikrotik e-module training is considered valid and practical.